Weathering and geochemical dispersion in Almirantazgo Bay, Crepin point, Machu Picchu Peruvian Antarctic station: preliminary results - Cerpa Cornejo, Luis Moroni; Morales Reyna, María del Carmen; Ng Cutipa, Wai Long; Ramos Palomino, Domingo A.; Masías Alvarez, Pablo Jorge (The Scientific Committee on Antarctic Research, 2015)
Global climate changes have a significant impact on the fragile ecosystems of Antarctica. These processes involve significant changes since the last glaciations, one product being exposure of areas with fracturing and weathering of rocks in Antarctica.The melting exposed surfaces of rocks, causing its disintegration due to physical or chemical and even organic processes; this decay involves the decomposition of minerals that are susceptible to these changes and tend to form new compounds. Undergoing environmental disturbances because of human disturbance, Antarctica is a suitable place to conduct a study on the geochemical characteristics of all elements present in the soil, which are closely related to the composition of the original rock. The preliminary reconnaissance and mapping of geological units were defined by Birkenmajer (1980) and subsequent work. Kraus et al., (2010) define regional geochemical characteristics and they related with paleomagnetism studies in across Almirantazgo Bay. Preliminary reconnaissance map in the Peruvian Antarctic Station was conducted by Palacios (1988) in the Antar II expedition; Geomorphological and stratigraphic units present were defined. Subsequent work performed in Crepin Point and vicinity were aimed at establishing the geotechnical characteristics (Fidel, 1991; Guzman, 1999; Pari & Zavala, 2000), mineralogical (Quispesivana, 1995; Aranda, 1997) and paleontological (Romero 2000; Morales 2002) they established and contributed the geological knowledge of Crepin Point. These studies recognized the presence of volcanic rocks, subvolcanic and intrusive nature that arise and are surrounded by glaciers. The volcanic rocks outcropping in the area are basaltic andesites and andesites. These are intruded by granodioritic intrusive rocks and subvolcanic dikes; both much younger. This process, where a young rock intrudes to an older, generates a chemical change in the contact zone of both bodies (Barnes, 1997). The changes are reflected when the original minerals, rocks both ...